Predictive Admission Risk Factors, Clinical Features and Kidney Outcomes in Covid-19 Hospitalised Patients with Acute Kidney Injury - Canevska Taneska, Aleksandra; Rambabova Bushljetic, Irena; Shterjova Markovska, Zhaklina; Milenkova, Mimoza; Vasileva, Adrijana Spasovska; Zafirova, Biljana; Pushevski, Vladimir; Severova Andreevska, Galina; Trajcheska, Lada; Spasovski, Goce (Macedonian Academy of Sciences and Arts/De Gruyter, 2023)
Introduction: In COVID-19 patients, acute kidney injury (AKI) is recognized as a cause of high mortality. The aim of our study was to assess the rate and the predictors of AKI as well as survival among COVID-19 patients. Methods: We analyzed clinical and laboratory admission data, predictors of AKI and outcomes including the need for renal replacement therapy (RRT) and mortality at 30 days. Results: Out of 115 patients, 62 (53.9%) presented with AKI: 21 (33.9%) at stage 1, 7(11.3%) at stage 2, and 34 (54.8%) at stage 3. RRT was required in 22.6% of patients and was resolved in 76%. Pre-existing CKD was associated with a 13-fold risk of AKI (p= 0.0001). Low albumin (p = 0.017), thrombocytopenia (p = 0.022) and increase of creatine kinase over 350UI (p = 0.024) were independently associated with a higher risk for AKI. Mortality rates were significantly higher among patients who developed AKI compared to those without (59.6% vs 30.2%, p= 0.003). Low oxygen blood saturation at admission and albumin were found as powerful independent predictors of mortality (OR 0.937; 95%CI: 0.917 - 0.958, p = 0.000; OR 0.987; 95%CI: 0.885-0.991, p= 0.024, respectively). Longer survival was observed in patients without AKI compared to patients with AKI (22.01± 1.703 vs 16.69 ± 1.54, log rank p= 0.009). Conclusion: Renal impairment is significant in hospitalized COVID-19 patients. The severity of the disease itself is emphasized as main contributing mechanism in the occurrence of AKI, and lower blood saturation at admission is the strongest mortality predictor, surpassing the significance of the AKI itself.
Keywords: COVID-19; AKI; predictors; mortality; admission; outcomes